Evaluation Of Image Enhancement Using Different Protocols For Routine Thorax Computed Tomography Examination On 16-Slice Scanners In Two Tertiary Hospitals - Ibrahim, Noor Ruhaya (2021)
The purposes of this study were to evaluate and compare the degree of contrast enhancement and image quality of routine thorax computed tomography (CT) examination on 16-slice scanner in two hospitals using two different protocols. The two protocols named as; 1) automatic bolus tracking (ABT), which volume of contrast media (CM) administered were tailored to the patient weight, known as weight-based volume, (WBV); 2) fixed time delay (FTD) technique, using the same delay for every patient and the patients were administered with fixed volume of contrast media (FV) regardless of their individual variations. Data of 140 patients were collected retrospectively from two centers; 70 patients were examined at Institut Perubatan dan Pergigian Termaju, Universiti Sains Malaysia (IPPT,USM), using ABT with WBV technique, and another 70 patients were examined at Hospital Pulau Pinang, Ministry of Health Malaysia (HPP, MoH) using FTD with FV technique. Patients from IPPT comprises of 19 males and 51 females; mean age ± standard deviation (SD) 53.6 ± 11.2 years; mean weight ± SD 54.04 ± 13.77kg. Patient from HPP comprises of 24 males and 46 females; mean age ± SD 54.5 ± 13.2 years. The degree of contrast enhancement in region of interest (ROI), were measured in Hounsfield unit (HU) values, for quantitative assessment. As for qualitative assessment, CT image were graded on 5 –point scale; 1= very poor, 2 = poor, 3 = fair, 4 = good, and 5 = excellent.